2008
DOI: 10.3892/mmr.1.3.347
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical profile of various neurotransmitters, neurotrophins and MIB-1 in cholesteatomas of the petrous bone

Abstract: Abstract. Compared to the normal epidermal epithelium, cholesteatomas have altered growth properties characterized by the excessive growth of keratinocytes leading to mucosal destruction. Either congenital or acquired, these lesions, which grow in the middle ear space, the petrous apex or the mastoid of temporal bones, are mostly considered benign skin tumoral lesions. However, many questions remain concerning their pathophysiology. Numerous studies have been proposed to identify those cholesteatoma lesions at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2010
2010
2012
2012

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…[19][20][21][22] A previous study identified the presence of neurotrophins in cholesteatoma. 23 These signaling molecules are capable of stimulating immune-mediated cells, such as macrophages, involved in the reabsorption of the bony covering.…”
Section: Discussionmentioning
confidence: 99%
“…[19][20][21][22] A previous study identified the presence of neurotrophins in cholesteatoma. 23 These signaling molecules are capable of stimulating immune-mediated cells, such as macrophages, involved in the reabsorption of the bony covering.…”
Section: Discussionmentioning
confidence: 99%
“…As we previously described, 15 Ki67 is a cell proliferation marker, utilized as a prognostic factor in the follow up of many neoplastic lesions, therefore our purpose was to analyze the expression level of MIB-1 (anti-Ki67) in the Reinke's edema samples, with the purpose of evaluate its biological role in this disease and its diagnostic application.…”
Section: Introductionmentioning
confidence: 99%
“…Since little is known about the pathological and histological differentiation among the benign and malignant forms of this tumor (malignancy is very rare), we decided to establish a panel of molecular factors, capable of better describing and clarifying this characterization. Therefore, as Yamamoto did previously (12), we investigated the expression of neurotrophins and their relative receptors in samples of benign jugulotympanic tumors and in normal and neoplastic non-neural tissues (19), to identify any direct involvement of these growth factors in the development of these neoplasms. In our surgical series, we selected intradural jugulotympanic tumors in order to analyse the clinical aggressiveness of these lesions comparing the proliferation rate of neutrophins expression and the incidence of recurrence.…”
mentioning
confidence: 98%
“…Although many pathologists include an assessment of MIB-l labeling in diagnostic profile of paragangliomas, there is currently no prospect of a standardization, and reporting a Ki-67 index still remains optional (18). Since we have previously described the role of MIB-l as a prognostic factor in other neoplasms (19), we decided to investigate this factor, supporting the results shown by Rodriguez, who first described (using immunohistochemical techniques) the presence and the localization of MIB-l in these tumors (8).…”
mentioning
confidence: 99%